Genomic editing with CRISPR/Cas9: Nobel Prize in Chemistry 2020 - Herrera-Cabrera, Braulio Edgar (2021)
The Royal Swedish Academy of Sciences awarded the 2020 Nobel Prize in Chemistry to two scientists, Dr. Emmanuelle Charpentier of the Max Planck Unit for Pathogen Science (Berlin, Germany), and Dr. Jennifer A. Doudna of the University of California (Berkeley, USA), for the development of a method for genome editing, one of the most resonant tools of the last decade: CRISPR/Cas9 genetic scissors. Nowadays, scientists can change the DNA of animals, plants and microorganisms with extremely high precision. The new CRISPR/Cas9 technology also has a revolutionary impact on human medicine, helping to generate new cancer therapies and even curing inherited diseases. The objectives of the present work are to mention the background, the importance of the discovery of genomic editing with CRISPR/Cas9, the molecular mechanism and the current applications of this valuable biotechnological tool in humans, animals, plants and microorganisms.